Utilizing Geophysical Methods for Geothermal Exploration - N Samsudin; N.M Muztaza; M.T Zakaria; T.O Adeeko; F Ahmad; M.H Arifin (Lowland Technology International, 2020)
Geothermal energy can be retrieved and simply generateenergy on par with the out-turn of other types of energyfabrication such as nuclear reactors due to its abundancy.Geothermal reservoirs are one of a naturally occurringhydrothermal resources. In this study, three geophysicalmethods were used to Pole-dipole array with an electrodespacing of 5 m was used during the application of 2-D electricalmethod meanwhile for magnetic method a proton precessionmagnetometer device and Global Positioning System (GPS)navigation were used when the method performed. Total of foursurvey lines were conducted for 2-D electrical and magneticmethod in which a data correlation between these two methodswill then be used for data interpretation. Inversion of apparentresistivity data to a 2-D electrical model section was done usinga RES2DINV software while for the magnetic data, MicrosoftExcels and Surfer 10 software was used and presented in aform of contouring in which discovered the fault zone. Analyticsignal map was produced from Surfer 10 and showing highmagnetic value in geothermal locality which is about >10 nTwhile resistivity gives a low value of 10 Ωm and IP shows highchargeability value of 40 msec. Increasing of iron oxide causingthe magnetic intensity to be high while increasing in temperatureresulted in low resistivity value. Most of the fractures occurred atdepth of 100 meters and above with size of approximately 20meters. The presence of fractures is associated with the majorfault in a geological map which occurred along the study area